Nilai-Nilai Pendidikan Islam dalam Ritual Pertanian Masyarakat Kasepuan Cicarucub Lebak Banten - Juju Juhariah; Wasehudin Wasehudin (Jurnal Ilmiah Wahana Pendidikan, 2023)
In the Kasepuhan Cicarucub group, Islamic education was shaped by two major factors: religious tradition and inherited cultural norms. They practice Islam but also hold fast to the traditions passed down from their ancestors. Their unique cultural practices, especially in agricultural, leadership, and human life cycle activities, give concrete form to the principles they espouse. Muslim schools in the Cicarucub ceremonial community teach its students to have faith, religious devotion, and moral principles. There was a preponderance of moral values over other values. In the same way that there was harmony, friendship, cooperation, care for others, and protection of the natural world. This means that for the Cicarucub people of Kasepuhan, religion and customs constitute the foundation of daily existence. There was so a balance between the two in their daily lives.